The Relationship Between Family Economic Level and the Incidence of Anemia in Pregnant Women - Huda Rohmawati; Nara Lintan Mega Puspita; Alfika Awatiszahro; Agung Nugroho (STRADA : Jurnal Ilmiah Kesehatan, 2024)
Nutritional Anemia is a health problem that plays a role in causing high Maternal Mortality Rates (MMR), Infant Mortality Rates (IMR) as well as low work productivity, sports performance and learning ability. Therefore, overcoming nutritional anemia is one of the potential programs to improve the quality of human resources, which has been implemented by the government since Long Term Development I. Research Objectives: To determine the relationship between the socio-economic level of the family and the incidence of anemia in pregnant women at RSIA Trisna Medika Tulungagung. The design used in this research is based on the scope of the research, including the type of inferential research. The research results showed that 13 (86.7%) respondents who had lower class economic status experienced pregnancy anemia.